Alcohol and older people: A systematic review of barriers, facilitators and context of drinking in older people and implications for intervention design. - Sarah Kelly; Olawale Olanrewaju; Andy Cowan; Carol Brayne; Louise Lafortune (PLoS ONE, 2018)
Background Harmful alcohol consumption in older people has increased and effective approaches to understanding and addressing this societal concern are needed. Methods Systematic review of qualitative studies in older populations (55+ years) to identify barriers, facilitators or context of drinking in older people. Multiple databases (MEDLINE, EMBASE, PsycINFO, CINAHL, CENTRAL, Social Sciences Citation Index, York Centre for Reviews and Dissemination, Cochrane database and grey literature) were searched from 2000 to February 2017 for studies in English, from OECD countries using MeSH terms and text words relating to alcohol combined with older age terms. Study quality was assessed using NICE methodology. The review is reported according to PRISMA. Results Drinking in older people is strongly linked to social engagement and there is scepticism about the health risks of alcohol. Drinking was also linked to difficulties such as social isolation, illness or bereavement. Alcohol can be related to routines and identity. However, older people often regulate their own drinking and strategies that emphasise the life experience of older people to drink wisely could be helpful. Conclusions To be effective societal approaches need to take into account contexts of risks for harmful drinking. The evidence supports a strong social role for drinking alcohol which should be taken into account in any policy development with the potential benefits of social participation for cognitive health. Approaches to reducing alcohol use in older people need to avoid paradoxical harm, with a need for approaches that reduce harm from drinking alcohol but retain the benefit of socialising.